Leadership factors affecting the success of technopreneurs in the United Arab Emirates - Alkhoori, Ahmed Abdulqader (2022)
Technopreneur's activities have contributed to both economic development and digital transformation. Nowadays, business firms are urged to play a proactive role in the issue of digital transformation through technopreneurship. In the UAE, digital entrepreneurship is at its infancy stage, in which most of the entrepreneurs regard digital transition as something new and they are not eagerly participated in it. Thus, as an initial step in developing a model of leadership factors affecting the success of technopreneurs in the UAE, this study was geared towards investigating the leadership factor’s intention towards successful technopreneurs. By integrating two popular intention-based models, the Transformational Leadership Theory and Theory of Planned Behaviors, this study attempted to explain the formation of intention towards leadership factors through digital enablers and entrepreneur skills. A conceptual model with six hypotheses were constructed to guide this study. This study employed a quantitative research method, in which questionnaires were used to collect data from 313 respondents among technopreneurs from the Innovation and Entrepreneur Centre, in Abu Dhabi. To empirically validate the model, the data were analysed statistically using Structural Equation Modelling (SEM). It was found that all the three variables, leadership factors, digital enablers and entrepreneurial skill have strong effect on the success of technopreneur, particularly the entrepreneurial skills have the strongest effect. It was also found that digital enablers have partial mediating effects, while the entrepreneurial skills have moderating effects on the relationship between the leadership factors and the success of technoprenuers in the UAE. As for the leadership factors, the devolved decision making, collaborative achievement, agility, purpose and direction, and authenticity were proven significantly and positively related to the success of technopreneurs. Theoretically, these findings support the Transformational Leadership Theory and Theory of Planned Behaviors that both digital enablers and entrepreneurial skills influenced the effect of leadership factors on the individual’s intention to become successful technopreneurs. This model is a useful guidance especially for the government of UAE that are undergoing a series of digital transformation process to become the next technology start-up hub by the year 2030.